Material requirements planning system: a case study of stationery manufacturer - Cheam, Kai Wen; Mohd Nor, Norasmiha; Taib, Muhammad Aidil; Rahman, Muhammad Saiful Syazuwan; Kor, Wan Xuan; Azman, Ameera Ainur (Penerbit UTHM, 2020)
Production planning and control system was essential to secure, reliable, and economic activity in an organization's manufacturing unit. Plan preparation and subsequent quality management follow the adaptation of the product design and development cycle finalization. Production planning and control is the methodology used to schedule every phase of a different project in a long cycle. Production planning and management help to make right decision in right place at right time, to achieve optimum efficiency (Juneja, 2020).